The Possible Innovative Use of Bifidobacterium longum W11 in Association With Rifaximin: A New Horizon for Combined Approach?. (November 2016) - Graziano, Teresa; Amoruso, Angela; Nicola, Stefania; Deidda, Francesca; Allesina, Serena; Pane, Marco; Piffanelli, Pietro; Strozzi, Francesco; Mogna, Luca; Del Piano, Mario
Abstract : Goals: The aim of the study was to unequivocally demonstrate the nontransmissibility of the genes mediating the resistance of the strain Bifidobacterium longum W11 (LMG P-21586) to rifaximin. Background: Most antibiotic treatments can induce unfavorable side effects such as antibiotic-associated diarrhea, which is largely attributable to the disruption of the intestinal microbiota. The parallel intake of probiotic bacteria might reduce these events, even if with generally very poor results. In this regard, the use of antibiotic-resistant beneficial bacteria could represent a worthy strategy. Study: Rifaximin was tested in parallel with rifampicin, rifapentine, and rifabutin, all rifamycin derivates, using 5 different concentrations. Susceptibility tests were performed by the disc diffusion method of Kirby-Bauer, and inhibition zones were measured after incubation at 37°C. B. longum BL03 was used as comparison. The B. longum W11 genome was sequenced on Illumina MiSeq with a 250 PE reads module. After mapping the reads with the reference bacterial genome, the alignment data were processed using FreeBayes software. Results: B. longum BL03 was inhibited by all antibiotics even at the lowest concentration. In contrast, the W11 strain was inhibited by rifampicin, rifabutin, and rifaximin only at the highest concentration (512 μg/mL). The genomic analysis showed a mutation into the chromosomal DNA. No transposable elements were found, and the genetic locus was not flanked by close mobile genetic elements. Conclusions: B. longum W11 could be used in combined therapy with rifaximin, thus opening new focused frontiers in the probiotic era while preserving the necessary safety of use for consumers.